Frameworks describing the transition to open labour employment for persons with mild and moderate intellectual disability: a scoping review protocol - Taryn Lynne du Toit; Mogammad Shaheed Soeker; Lisa Wegner (BMJ Open)
Introduction Persons with mild and moderate intellectual disability (MMID) have the right to participate in all aspects of society and be afforded equal opportunities to realise their full potential. However, it is a challenge for persons with MMID to find and maintain employment due to many different barriers. Currently, there is no contextually relevant framework in South Africa that considers the unique employment support needs and accommodation of persons with MMID, which can guide and inform the transition to employment interventions, strategies and national policy directives.Methods and analysis The proposed scoping review will be guided by the methodological framework developed by a working group from the Joanna Briggs Institute (JBI) and the JBI Collaboration. The search for relevant studies will be conducted across 12 research databases. Reference mining of review studies will be conducted. A three-step search strategy will be used, including the use of information management software to manage the search results. Three independent reviewers will screen the full-text studies to finalise the list of included and excluded studies. Included studies will be assessed for methodological quality using a critical appraisal tool. Data will be charted by one independent reviewer and assessed by two independent reviewers, using a data charting instrument. The data chart will be presented using tables and charts describing the demographic features of the reviewed studies, with an explanation of the thematically analysed results.Ethics and dissemination This scoping review has received ethical approval (BM22/10/11). A summary of the findings of the study will be published in a peer-reviewed journal. This scoping review will contribute to a better understanding of the key characteristics or factors underpinning the components of a multilevel transition to employment framework that will result in open labour market employment for persons with MMID.